2014
DOI: 10.1016/j.foreco.2013.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in understory woody diversity and soil nitrogen across native- and non-native-urban tropical forests

Abstract: Urban expansion is accelerating in the tropics, and may promote the spread of introduced plant species into urban-proximate forests. For example, soil disturbance can deplete the naturally high soil nitrogen pools in wet tropical soils, favoring introduced species with nitrogen-fixing capabilities. Also, forest fragmentation and canopy disturbance are likely to favor high-light species over shade-adapted rainforest species. We measured understory woody diversity, the abundance of introduced species, and soil n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 58 publications
(73 reference statements)
0
19
0
1
Order By: Relevance
“…Although it is a macronutrient, adding nitrogen to secondary tropical forests is thought to enhance tropical forest growth, but it can also inhibit growth [120,121]. In addition, increasing the basal area of N-fixing trees, including exotic species or species other than legumes, increases nitrogen levels in leaf litter, forest floor organic matter, or soils, and soils of secondary tropical forests release more NOx to the atmosphere [28,87,104,109,122], and NOx's are potent greenhouse gases. The maps here illustrate where N-fixing species are most abundant.…”
Section: Implications For Sustainable Development Goal Indicatorsmentioning
confidence: 99%
“…Although it is a macronutrient, adding nitrogen to secondary tropical forests is thought to enhance tropical forest growth, but it can also inhibit growth [120,121]. In addition, increasing the basal area of N-fixing trees, including exotic species or species other than legumes, increases nitrogen levels in leaf litter, forest floor organic matter, or soils, and soils of secondary tropical forests release more NOx to the atmosphere [28,87,104,109,122], and NOx's are potent greenhouse gases. The maps here illustrate where N-fixing species are most abundant.…”
Section: Implications For Sustainable Development Goal Indicatorsmentioning
confidence: 99%
“…In a Puerto Rican study, secondary forests with substantial numbers of exotic trees in the canopy (i.e., novel species composition) had less aboveground biomass than native secondary forests of similar age, although much of the difference was attributed to past land use [ Lugo and Helmer , ]. Another Puerto Rican study found no significant relationship between stem biomass and the proportion of exotic tree species in the canopy [ Cusack and McCleery , ]. Because of the limited number of studies on biomass in exotic‐dominated versus native‐dominated secondary forests on abandoned lands, and because of the many site and land use history factors affecting rates of plant growth and biomass accumulation, it is difficult to generalize whether invasive tropical trees generally decrease C stocks in novel secondary forests relative to native secondary forests.…”
Section: Review Of Global Change Effects On Tropical Ecosystemsmentioning
confidence: 99%
“…For example, secondary forests along an urban‐rural gradient in Puerto Rico showed very high variability in soil N levels among nearby secondary forest stands [ Cusack , ]. In these sites, some of the spatial variability in soil N was related to varying abundances of exotic N‐fixing trees across secondary forests [ Cusack and McCleery , ], with additional variability likely caused by differences in land use history.…”
Section: Review Of Global Change Effects On Tropical Ecosystemsmentioning
confidence: 99%
“…All forest stands were secondary regeneration following widespread agricultural abandonment in Puerto Rico starting in the 1930s (Kennaway & Helmer, 2007). Both the Rio Piedras and Cubuy forests contained novel mixtures of native and non-native tree species (Helmer, 2004;Lugo, 2004;Kennaway & Helmer, 2007;Cusack & McCleery, 2014). Abundant exotic grass species in the urban watershed included Panicum maximum Jac q. and Pennisetum purpureum Schumach., which are both African grasses and can establish in open areas (Lugo et al, 2001).…”
Section: Study Sitesmentioning
confidence: 99%
“…However, the potential for recovery of lost soil C, even after long-term forest regeneration, varies greatly across sites with no clear trends (Powers, 2004;Jimenez et al, 2008;Marin-Spiotta & Sharma, 2013). Also, many abandoned lands are relatively near urban centers and are within the range of current urban expansion, such that secondary forests are subject to ongoing disturbances such as clearing, exotic species establishment, and N deposition (Chytry et al, 2008;Cusack & McCleery, 2014).…”
Section: Introductionmentioning
confidence: 99%